Transferrin Receptor Is a Specific Ferroptosis Marker - Feng, Huizhong; Schorpp, Kenji; Jin, Jenny; Yozwiak, Carrie E.; Hoffstrom, Benjamin G.; Decker, Aubrianna M.; Rajbhandari, Presha; Stokes, Michael E.; Bender, Hannah G.; Csuka, Joleen M.; Upadhyayula, Pavan S.; Canoll, Peter; et al. (Cell reports (Cambridge), 2020)
Ferroptosis is a type of regulated cell death driven by the iron-dependent accumulation of oxidized polyunsaturated fatty acid-containing phospholipids. There is no reliable way to selectively stain ferroptotic cells in tissue sections to characterize the extent of ferroptosis in animal models or patient samples. We address this gap by immunizing mice with membranes from lymphoma cells treated with the ferroptosis inducer piperazine erastin and screening ∼4,750 of the resulting monoclonal antibodies generated for their ability to selectively detect cells undergoing ferroptosis. We find that one antibody, 3F3 ferroptotic membrane antibody (3F3-FMA), is effective as a selective ferroptosis-staining reagent. The antigen of 3F3-FMA is identified as the human transferrin receptor 1 protein (TfR1). We validate this finding with several additional anti-TfR1 antibodies and compare them to other potential ferroptosis-detecting reagents. We find that anti-TfR1 and anti-malondialdehyde adduct antibodies are effective at staining ferroptotic tumor cells in multiple cell culture and tissue contexts. [Display omitted] •3F3-FMA is identified in a screen as a selective ferroptosis-immunostaining reagent•The antigen of 3F3-FMA is identified as the transferrin receptor 1 protein (TfR1)•Anti-TfR1 antibodies can detect ferroptosis by immunofluorescence and flow cytometry•Anti-TfR1 and anti-MDA antibodies detect ferroptosis in xenograft cancer models Feng et al. find that 3F3-FMA detects ferroptotic cells by screening ∼4,750 antibodies generated from mice immunized with membranes from DLBCL cells undergoing ferroptosis. The antigen of 3F3-FMA is the TfR1 protein. 3F3-FMA and other anti-TfR1 antibodies can be used to detect ferroptosis in cell culture and in cancer models.